A ideologia da racionalidade tecnológica, o narcisismo e a melancolia: marcas do sofrimento - Pedrossian, Dulce Regina dos Santos (2005)
The purpose of this study is to verify the relationship between narcissism, melancholy and the ideology of the technological rationality by means of some mediator concepts, for instance cultural industry, mass phenomena, that tend to reproduce the social dominance in a number of instances of an individual s life in our present society. It is a theoretical research that attempts to conduct the reflection on the tensions that exist among individual, nature, society and culture, using mainly the analyses of Theodor W. Adorno, Max Horkheimer, Herbert Marcuse and Sigmund Freud. The main results accomplished were: 1. Melancholy is a form through which narcissism manifests itself; every melancholy has some marks of narcissism. On its turn, narcissism is present in melancholy, but not only in it, and the narcissistic - including the manipulator type -, melancholic, compulsive and sadomasochistic conformations have a certain relationship and are associated with the irrational defense of the technique. 2. Both in narcissism and in melancholy it is present the ego weaknessing and the psychic regression in face of the need of self-conservation in the contemporary society. 3. The individual identifies a lot with the current culture that benefits the narcissism, so that cruelty, indifference and unawareness are indications that the claustrophobia of the society and the social hibernation reflect in the individual. 4. No matter how much the individual\'s conscience is mediated by the society, the critical reason, as opposed to the formalized reason, functionalized and subjective, may serve as a defense against the inner and outer miseries. We hope that this thesis encourages the completion of further researches, in particular the ones of empiric character.